Fenomena Lunturnya 3 Makna Kata (Tolong, Maaf dan Terimakasih) dalam Etika Komunikasi di Kota Medan - Pohan, Syafruddin; Ariftha, Annisa; Ramadhan, All Rizky; Afif, Ahmad Saleh (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The city of Medan, as a center of rapidly developing social and economic activity, is experiencing an interesting phenomenon related to the erosion of the meaning of words in communication ethics, namely "please," "sorry," and "thank you." This research tries to explore this. First, the word “help” has softened into a mere word of politeness, losing its essence as an act of empathy and cooperation. People often ask for “help” without actually expecting concrete help, creating ambiguity in social interactions. Second, “sorry” is often used routinely, without a deep understanding of guilt or regret. This phenomenon shows a lack of responsibility in communication, where apologies are often just a formality without meaning. Third, "thank you" has become a sign of gratitude that loses its meaning, often said hastily and without any sense of sincerity. This reflects a decline in appreciation for social assistance and cooperation. These three phenomena reflect a cultural shift in communication ethics in the city of Medan. Further research is needed to understand the impact of the erosion of the meaning of these words on the quality of social interactions and how they can be restored to more meaningful use in everyday communication.